2022
DOI: 10.1371/journal.pone.0262335
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of Zingiber ottensii essential oil and its nanoformulations

Abstract: Zingiber ottensii, is widely used in Asian traditional remedies for the treatment of many diseases. The present study explores anticancer activity of Z. ottensii essential oil (ZOEO) and its nanoformulations. ZOEO obtained from hydrodistillation of Z. ottensii fresh rhizomes was analysis using gas chromatography mass spectroscopy. Zerumbone (25.21%) was the major compound of ZOEO followed by sabinene (23.35%) and terpene-4-ol (15.97%). Four types of ZOEO loaded nanoformulations; nanoemulsion, microemulsion, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…All essential oil samples displayed significant cell proliferation activity, in which the growth of the HeLa cells declined in a dose-dependent manner ( Figure 3 ). This result is in agreement with a study reported by Panyajai et al, where the oil of Zingiber ottensii also showed dose-dependent anticancer activity against the HeLa cell line [ 44 ]. The highest antiproliferative activity was shown by BA oil (IC 50 = 23.8 μg/mL), followed by BE (IC 50 = 35.3 μg/mL), SA (IC 50 = 41.3 μg/mL), and CH (IC 50 = 42.5 μg/mL).…”
Section: Resultssupporting
confidence: 93%
“…All essential oil samples displayed significant cell proliferation activity, in which the growth of the HeLa cells declined in a dose-dependent manner ( Figure 3 ). This result is in agreement with a study reported by Panyajai et al, where the oil of Zingiber ottensii also showed dose-dependent anticancer activity against the HeLa cell line [ 44 ]. The highest antiproliferative activity was shown by BA oil (IC 50 = 23.8 μg/mL), followed by BE (IC 50 = 35.3 μg/mL), SA (IC 50 = 41.3 μg/mL), and CH (IC 50 = 42.5 μg/mL).…”
Section: Resultssupporting
confidence: 93%
“…The marked elevations in ROS levels in cells treated with Oxa + TPO-NANO and TPO-NANO, relative to cells treated with Oxa-NS might be explained by the apoptotic potential of these two formulations on the studied cancer cells. Previous studies have demonstrated the anticancer potential of essential oils formulated into nanocarriers which predominantly triggered ROS production within cancer cells, thereby facilitating apoptosis of the treated cells (Al-otaibi, 2021 ; AlMotwaa, 2021 ; Salehi et al., 2020 ; Panyajai et al., 2022 ; Nirmala et al., 2020 ). Furthermore, TPO and its bioactive components have been shown to exert anticancer potential predominantly by induction of ROS generation and induction of cell death through the mitochondria-mediated apoptotic pathway (Su et al., 2013 ; Bai & Tang, 2020 ; Li et al., 2013 ; Sobral et al., 2014 ; Pan et al., 2016 ; Karan et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…They obtained the greatest apoptotic action against MCF-7 breast cancer cells with the drug incorporated into lemon or salvia EO-based nanoemulsion, suggesting an enhanced solubilizing of the drug with this formulation. Recently, Panyajai et al [ 181 ] developed nanoformulations that significantly enhance the anticancer effects, especially against MCF-7, and show a superior internalization into cancer cells.…”
Section: Targeted Nanodelivery Systems For Anticancer Applicationsmentioning
confidence: 99%